Stroke in COVID-19: a single-centre initial experience in a hotspot of the pandemic. Issue 4 (24th September 2020) - Bach, Ivo; Surathi, Pratibha; Montealegre, Nora; Abu-Hadid, Osama; Rubenstein, Sara; Redko, Sviatoslav; Gupta, Siddharth; Hillen, Machteld; Patel, Pratit; Khandelwal, Priyank; Kamel, Adham
Abstract : Background: COVID-19, caused by SARS-CoV-2, is a global pandemic that has been an immense burden on healthcare systems all over the world. These patients may be at higher risk for acute ischaemic stroke (AIS). We present our experience with AIS in patients with COVID-19. Methods: We reviewed all patients admitted to our hospital during a 6-week period with a positive nasopharyngeal swab test for SARS-CoV-2. Among these patients, we identified AIS. We reviewed the demographics, clinical, laboratory, imaging characteristics, treatments received and outcomes of AIS in patients with COVID-19. Results: We identified 683 patients admitted with COVID-19 during the study period, of which 20 patients had AIS. Large-vessel occlusion (LVO) was noted in 11 patients (55%). Intravenous alteplase was administered in four patients (20%) and mechanical thrombectomy was performed in five patients (25%). Respiratory symptoms preceded the onset of AIS in most of the patients (70%) by 1 to 21 days. Mortality in patients with AIS was 50% compared with 26% of all COVID-19 admissions. Most of these patients died due to non-neurological causes (70%). Three patients with AIS had clinical and imaging findings consistent with COVID-19, but were negative for multiple nasopharyngeal swab tests. Interpretation: LVO was more common in patients with AIS and COVID-19. They had more severe disease and higher mortality rates. Most of the patients had respiratory symptoms preceding AIS by days to weeks. This could explain certain patients with clinical picture of COVID-19 but negative nasopharyngeal swab tests.